Prevalence of adolescent obesity among high school students of Kerala, South India - Ambili Remesh (Archives of Global Professionals, 2012)
Objectives: To study the prevalence of obesity among high school students of age 15-17 years and identify the associated risk factors. Materials and Methods: A descriptive cross-sectional study involving the measurement of height and weight and calculation of body mass index among high school students of Kottukal and Pallichal localities of Trivandrum districts in Kerala, South India. A study questionnaire was administered among the participants and their parents to understand the relationship of food intake, parental obesity, and physical activity to obesity. Results: Of the 560 students enrolled, 49 (8.75%) were overweight and 27 (4.82%) were obese. With this, the prevalence of obese is computed as 4.8%. The parental obesity posed a significant risk factor among the study population. Conclusion: Creating awareness among adults and school-goers on the negative health effects of obesity, the key for maintaining good health.